1959
DOI: 10.1039/df9592700129
|View full text |Cite
|
Sign up to set email alerts
|

Charge transfer processes in biological systems

Abstract: The biological effects of radiation are discussed in relation to long-lived excited states, involving v electron rearrangements, in proteins. The increase in radiosensitivity which oxygen and nitric oxide confer on a number of biological systems is attributed to their perturbation of singlet-triplet transitions while the radiobiological effects of the inert and a number of other gases may derive from their collisional deactivation of the triplet states.The specificity of action of aromatic hydrocarbons is foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

1961
1961
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 3 publications
1
6
0
Order By: Relevance
“…Besides the other evidence already mentioned for electron tunneling in molecular processes (44, 48, 49), we may cite also the observation that electron exchange takes place between gaseous ions and their neutral gaseous parent molecules over distances of approach almost twice as large as those required for momentum transfer in collisions (66,67). A correlation has been made between carcinogenicity of hydrocarbons and their fluorescence spectra which indicate a requirement that energy levels be matched (22,26). Such a requirement would be expected if the process were one of electron transfer by tunneling.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…Besides the other evidence already mentioned for electron tunneling in molecular processes (44, 48, 49), we may cite also the observation that electron exchange takes place between gaseous ions and their neutral gaseous parent molecules over distances of approach almost twice as large as those required for momentum transfer in collisions (66,67). A correlation has been made between carcinogenicity of hydrocarbons and their fluorescence spectra which indicate a requirement that energy levels be matched (22,26). Such a requirement would be expected if the process were one of electron transfer by tunneling.…”
Section: Discussionsupporting
confidence: 59%
“…The literature was reviewed to determine what mechanisms for electron transfer have been proposed that might have some bearing on the process studied here. Szent-Gyorgyi (19) suggested that biological systems may act as semiconductors and many have followed this idea (20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). However, the measured activation energies are above 1 or 2 ev for biological material (20,(22)(23)(24)(25)(26)(27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Charge transfer (CT) excitation energy calculation has gained much attention in materials and biological sciences [1][2][3] . In a spatially separated donor-acceptor (D-A) system with intermolecular distance R, the CT excitation process involves electron transition from donor molecule (D) to acceptor molecule (A), and the CT excitation energy at asymptotically large R is given by…”
Section: Introductionmentioning
confidence: 99%
“…Charge transfer (CT) excitations are frequently encountered in materials and biological sciences. [1][2][3][4] They play an important role in electron transfer and energy conversion. Therefore, it is highly desirable to understand and describe CT excitations well.…”
Section: Introductionmentioning
confidence: 99%